Comparison of the efficacy and safety of CELBESTA® versus CELEBREX® in patients with rheumatoid arthritis: a 6-week, multicenter, double-blind, double-dummy, active-controlled, randomized, parallel-group, non-inferiority phase 4 clinical trial - Kim, Hyun-Sook; Choi, Won-Ho; Kim, Bo Young; Kim, Sung Soo; Lee, Sang-Il; Kim, Sang-Hyon; Choi, Sung Jae; Kim, Geun-Tae; Hur, Jin-Wuk; Lee, Myeung-Su; Kim, Yun Sung; Hong, Seung-Jae (Journal of international medical research, 2020)
Objectives Celecoxib is a selective cyclooxygenase (COX)-2 inhibitor that is commonly used to reduce the incidence of gastrointestinal (GI) complications in patients with rheumatoid arthritis (RA). CELBESTA® is a generic equivalent to CELEBREX®, a celecoxib preparation. This study compared the efficacy and safety of CELBESTA® and CELEBREX® in patients with RA. Methods This was a multicenter, double-blind, double-dummy, active-controlled, randomized, parallel-group, non-inferiority clinical trial. The primary endpoint was a change from baseline in self-assessed pain intensity determined using a 100-mm visual analog scale after 6 weeks of treatment. Results After a washout period, 119 eligible subjects were randomized to one of two groups (CELBESTA® group, n = 61; CELEBREX® group, n = 58). CELBESTA® was not inferior to CELEBREX® because the upper limit of two-sided 95% confidence interval (CI) for the difference between the two groups (difference in the least square [LS] mean, −8.68 mm; two-sided 95% CI −16.59 mm to −0.77 mm) was less than the non-inferiority margin (10 mm). There were no significant differences in GI complications and renal toxicity. Conclusions CELBESTA® was not inferior to CELEBREX® with regard to the pain relief efficacy in RA patients, and the tolerability and safety profiles were excellent and at similar levels for both preparations.